A New Methodology of Viewing Extra-Axial Fluid and Cortical Abnormalities in Children with Autism via Transcranial Ultrasonography - Bradstreet, James J.; Pacini, Stefania; Ruggiero, Marco (Frontiers in Human Neuroscience, 2014)
Background: Autism spectrum disorders (ASDs) are developmental conditions of uncertain etiology which have now affected more than 1% of the school-age population of children in many developed nations. Transcranial ultrasonography (TUS) via the temporal bone appeared to be a potential window of investigation to determine the presence of both cortical abnormalities and increased extra-axial fluid (EAF). Methods: TUS was accomplished using a linear probe (10-5 MHz). Parents volunteered ASD subjects (N = 23; males 18, females 5) for evaluations (mean = 7.46 years + 3.97 years), and 15 neurotypical siblings were also examined (mean = 7.15 years + 4.49 years). Childhood Autism Rating Scale (CARS2®) scores were obtained and the ASD score mean was 48.08 + 6.79 (Severe). Results: Comparisons of the extra-axial spaces indicated increases in the ASD subjects. For EAF we scored based on the gyral summit distances between the arachnoid membrane and the cortical pia layer (subarachnoid space): 1) < 0.05 cm, 2) 0.05 – 0.07 cm, 3) 0.07 – 0.10 cm, 4) > 0.10 cm. All of the neurotypical siblings scored 1, whereas the ASD mean score was 3.41 + 0.67. We also defined cortical dysplasia as the following: hypoechoic lesions within the substance of the cortex, or disturbed layering within the grey matter. For cortical dysplasia we scored: 1) none observed, 2) rare hypoechogenic lesions and/or mildly atypical cortical layering patterns, 3) more common, but separated areas of cortical hypoechogenic lesions, 4) very common or confluent areas of cortical hypoechogenicity. Again all of the neurotypical siblings scored 1, while the ASD subjects’ mean score was 2.79 + 0.93. Conclusions: TUS may be a useful screening technique for children at potential risk of ASDs which, if confirmed with repeated studies and high resolution MRI, provides rapid, noninvasive qualification of EAF and cortical lesions.